Analisis penerimaan pajak daerah dan pengaruhnya terhadap belanja daerah Provinsi Jambi - Hariansyah, Zuhri; Syurya Hidayat , M.; Achmad, Erni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The purpose of this study is to find out and analyze the development of regional tax revenues and regional original revenues of Jambi Province in 2009-2020, to find out and analyze which types of local taxes have the potential to be developed in Jambi Province in 2009-2020, to determine and analyze the effect of indicated local taxes. the potential for regional expenditures in Jambi Province in 2009-2020 and analyze the potential tax increase strategy of Jambi Province. This type of research is quantitative research and the analytical tools used are simple linear regression and SWOT analysis. Based on the results of research on Motor Vehicle Tax and Tax Transfer of Ownership of Motor Vehicles which have the potential to be developed, have a significant effect on regional spending in Jambi Province. Based on the results of the SWOT analysis, it can be concluded that the right strategy to increase the Motor Vehicle Tax and the Transfer of Title Tax for Motor Vehicles which are potential taxes is the SO strategy. The SO strategy is to improve the quality of human resources or apparatus, improve service performance to the community, optimize the use of computer facilities and coordinate with the team to intensify the collection of Motor Vehicle Taxes and Motor Vehicle Transfers.